Soccer players' fitting perception of different upper boot materials - Olaso Melis, J. C.; Priego Quesada, J. I.; Lucas-Cuevas, A. G.; Gonzalez Garcia, J. C.; Puigcerver Palau, S. (Applied Ergonomics, 2016)
Soccer players' fitting perception of different upper boot materials were assessed. The type of leather of the upper boot influences the fitting perception. The kangaroo leather was perceived as the closest condition to the preferred fitting. The synthetic leather was perceived as the furthest condition to the preferred fitting. These results are relevant to the comfort and fit of players and purchase decision-making. The present study assessed the influence of upper boot materials on fitting perception. Twenty players tested three soccer boots only differing in the upper boot material (natural calf leather, natural kangaroo leather and synthetic leather). Players reported fitting perception and preference on specific foot areas using a perceived fitting scale. Ratings were averaged for every foot area. Repeated measures ANOVA was used to analyze the differences between boots. The kangaroo leather boots were perceived tighter and closer to the preferred fitting in general fitting, metatarsals area and instep area. The synthetic leather boots were perceived as the loosest and as the most distant boot from the preferred fitting in medial front area and instep area. In conclusion, the type of upper boot material influences the fitting perception of soccer players. The kangaroo leather was the material whose fitting was perceived closest to the players fitting preference.